"As in a Civics Text Come to Life": The East Brooklyn Congregations' Nehemiah Housing Plan and "Citizens Power" in the 1980s. (September 2019) - Deslippe, Dennis
In the early 1980s the East Brooklyn Congregations (EBC) began to build the first of 4, 500 affordable, single-family homes, known as Nehemiah Houses. This essay examines how the EBC's many trained local clergy and lay church members forged a potent body of ideas that drew on civic republicanism, nineteenth century populism, and the rich religious traditions of neighborhood churches to bring about the localization of author and decision making in the Plan's rationale, design, building, process, and price. I argue that, as a "citizens power organization, " it succeeded in countering neoliberal solutions to urban decline that focused on privatization, deregulation, and subsidies to private developers. The adoption of the Nehemiah Plan elsewhere illustrates the cross-fertilization among citizen power organizations. In turn, the EBC took up new projects for East Brooklyn, including a living wage campaign launched first in Baltimore in the early 1990s.